Effects of dark chocolate on NOX‐2‐generated oxidative stress in patients with non‐alcoholic steatohepatitis. Issue 3 (6th June 2016) - Loffredo, L.; Del Ben, M.; Perri, L.; Carnevale, R.; Nocella, C.; Catasca, E.; Baratta, F.; Ceci, F.; Polimeni, L.; Gozzo, P.; Violi, F.; Angelico, F.
Summary: Background: Activation of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase is considered a pathogenetic mechanism determining fibrosis and disease progression in non‐alcoholic steatohepatitis (NASH). Polyphenols exert antioxidant action and inhibit NADPH oxidase in humans. Aim: To analyse the effect of cocoa polyphenols on NADPH oxidase isoform 2 (NOX2) activation, oxidative stress and hepatocyte apoptosis in a population affected by NASH. Methods: In a cross‐sectional study comparing 19 NASH and 19 controls, oxidative stress, as assessed by serum NOX2 activity and F2‐isoprostanes, and hepatocyte apoptosis, as assessed by serum cytokeratin‐18 (CK‐18) levels, were measured. Furthermore, the 19 NASH patients were randomly allocated in a crossover design to 40 g/day of dark chocolate (>85% cocoa) or 40 g/day of milk chocolate (<35% cocoa), for 2 weeks. sNOX2‐dp, serum isoprostanes and CK‐18 were assessed at baseline and after 2 weeks of chocolate intake. Results: Compared to controls, NASH patients had higher sNOX2‐dp, serum isoprostanes and CK‐18 levels. A significant difference for treatments was found in subjects with respect to sNOX2‐dp, serum isoprostanes and serum CK‐18. The pairwise comparisons showed that, compared to baseline, after 14 days of dark chocolate intake, a significant reduction in sNOX2‐dp serum isoprostanes and CK‐18 M30 was found. No change was observed after milk chocolate ingestion. A simple linear regression analysis showed that ∆ of sNOX2‐dp was associated with ∆ of serum isoprostanes. Conclusion: Cocoa polyphenols exert an antioxidant activity via NOX2 down‐regulation in NASH patients.